REPRODUCTIVE PERFORMANCE OF ANESTROUS NON-DESCRIPTIVE COWS TREATED WITH CIDR AND PGF2alpha - VIJAYARAJAN, A; MEENAKSHISUNDARAM, S (The Indian Journal of Animal Reproduction, 2023)
The present clinical study was carried out to evaluate the reproductive performance in non descriptive cows using (CIDR) and PGF2 a under field condition. The cows were divided into two groups comprising of 12 cows in each group. Group I animals (n= 12) served as control and were inseminated during natural estrus and in group II cows (n= 12) estrous cycle was induced by inserting CIDR for9 days and PGF2 a was given intramuscularly 24 hrs prior to CIDR removal. Fixed time artificial insemination was carried out at48 and 72 hrs after CIDR removal. The overall conception rate obtained was 41.66 % in group I animals and 91.66 % in group 11 animals treated with Cl DR and PGF2alpha.